2020
DOI: 10.1002/psp4.12521
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Exposure–Response of Luspatercept, an Erythroid Maturation Agent, in Anemic Patients With Myelodysplastic Syndromes

Abstract: Luspatercept is a recombinant fusion protein that enhances late‐stage erythroid maturation. This report describes the population pharmacokinetics and exposure–response relationship of luspatercept in 260 patients with anemia due to myelodysplastic syndromes. Luspatercept displayed linear and time‐invariant pharmacokinetics over a dose range of 0.125–1.75 mg/kg administered subcutaneously once every 3 weeks. Body weight was the only clinically relevant covariate of luspatercept exposure, supporting the weight‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Inspection of cumulative events for the 2 TEAEs over time during the entire study found that the increased TEAEs were mainly observed in the lower‐exposure groups; the incidence of the event was substantially lower in the highest AUC TEAE group compared with the lowest AUC TEAE group at most times. An inverse exposure‐TEAE relationship for luspatercept was also observed in other study populations 11 . The exposure‐TEAE relationship for the entire study could be confounded by dose increases over time or by individual variations in the treatment duration, during which certain adverse events manifest.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Inspection of cumulative events for the 2 TEAEs over time during the entire study found that the increased TEAEs were mainly observed in the lower‐exposure groups; the incidence of the event was substantially lower in the highest AUC TEAE group compared with the lowest AUC TEAE group at most times. An inverse exposure‐TEAE relationship for luspatercept was also observed in other study populations 11 . The exposure‐TEAE relationship for the entire study could be confounded by dose increases over time or by individual variations in the treatment duration, during which certain adverse events manifest.…”
Section: Discussionsupporting
confidence: 59%
“…An inverse exposure-TEAE relationship for luspatercept was also observed in other study populations. 11 The exposure-TEAE relationship for the entire study could be confounded by dose increases over time or by individual variations in the treatment duration, during which certain adverse events manifest. Such an explanation is not considered likely for the current analysis, as the small dose increase (25%) fell within the individual exposure variability (36%) and the number of patients across AUC TEAE groups during the entire evaluation period was similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13 Interestingly, apparent CL was strongly associated with efficacy for luspatercept, a therapeutic protein investigated in the MDS population, suggesting possible CL associations with severity of disease/anemia in MDS and providing support for these postulations. 43 However, it cannot be excluded that the identified time effect in this analysis may reflect fitting criteria to improve model description of the available data. The identification of dose as a covariate likely reflects additional nonlinearity in The simulated imetelstat concentration-time characterizes a biphasic elimination profile and shows an overall rapid disappearance plasma with an apparent t 1/2 , defined as the model estimated time for imetelstat concentrations to decrease by 50%, of 4.9 h, thus likely reflecting the rapid initial disposition phase (Figure S18).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a near-maximal response was correlated with AUC avg values ≥150 day•μg/ml irrespective of dose escalation status. 8…”
Section: Pharmacodynamics/pharmacokineticsmentioning
confidence: 99%